PENGEMBANGAN ALAT PENGUPAS ROTAN SEMI OTOMATIS UNTUK MENINGKATKAN EFISIENSI PRODUKSI DAN KESEJAHTERAAN PENGRAJIN ROTAN - Imansyah, Fitri; Djanggu, Noveicalistus H.; Prima, Febri; Sujana, Ivan (Universitas Mataram, 2024)
Crafts made from rattan plants have very high economic value. To produce high-quality rattan products, several lengthy stages are required before they can be sold to buyers. One of the time-consuming stages for craftsmen is the raw material preparation stage. In this stage, the outer skin of the rattan is removed or scraped off using a blade to obtain a smooth rattan surface and ensure a uniform diameter. This factor causes many community members who are also craftsmen to be reluctant to produce rattan crafts; instead, they prefer to sell the raw rattan material directly to neighboring countries, which is illegal. The development of a semi-automatic rattan peeler aims to improve production efficiency and the welfare of rattan craftsmen in Indonesia. The manual rattan peeling process that craftsmen have been using often takes a long time, requires significant physical effort, and carries a high risk of work-related injuries. This research developed a semi-automatic rattan peeler designed to address these issues. The test results showed that this tool could increase the peeling speed up to twice compared to manual methods, produce more consistent peeling, and reduce the risk of injury. This efficiency improvement directly contributes to increased productivity and income for craftsmen, ultimately enhancing their welfare. Furthermore, the quality of the rattan produced also improves, adding value to Indonesian rattan products in domestic and international markets. The use of this tool also supports more environmentally friendly production practices by reducing waste. In conclusion, the development of this semi-automatic rattan peeler has a significant positive impact on various aspects of production and the welfare of craftsmen, as well as strengthening the competitiveness of Indonesian rattan products in the global market.